Impact of malnutrition on health‐related quality of life in patients on maintenance hemodialysis. Issue 4 (20th November 2020) - Nagy, Eman; Mahmoud, Mostafa; El‐kannishy, Ghada; Sayed‐Ahmed, Nagy
Abstract: Malnutrition is considered as one of the most important risk factors that adversely affect the quality of life (QOL) in maintenance hemodialysis (MHD) patients. Many clinically useful nutrition assessment techniques are now available, but the usefulness of such techniques in predicting QOL in MHD patients had not been sufficiently tested. The aim of this study was to explore the relation between different nutritional assessment methods, and QOL and identify nutritional parameter that can best predict physical and mental domains of QOL in MHD patients. This cross‐sectional study involved 84 MHD patients. Nutritional status was assessed by using International Society of Renal Nutrition and Metabolism criteria for diagnosis of protein‐energy wasting (PEW), malnutrition inflammation score (MIS), subjective global assessment (SGA), anthropometric measurements, bioelectrical impedance analysis, and biochemical tests. Quality of life was evaluated by using the Kidney Disease Quality of Life (36 KDQOL‐36). Only mental health composite component of QOL (MHC) showed statistically significant differences between PEW and non‐PEW groups. MHC was correlated with serum albumin, MIS, and SGA. Physical health composite component (PHC) was correlated with age, hemodialysis duration, socioeconomic status, comorbidity, educational level, serum creatinine and ferritin, MIS, and SGA. On multiple linear regression analysis, MIS was found to be the most significant predictor of PHC while none of the nutritional parameters can predict MHC. Malnutrition is not uncommon problem in MHD patients that is associated with poor QOL. There are multiple factors associated with PHC and only malnutrition afflicts MHC in those patients.